NUMERICAL INVESTIGATION ON HEMODYNAMICS AND PLATELET ACTIVATION POTENTIAL OF BILEAFLET MECHANICAL HEART VALVES - ABBAS, SYED SAMAR (2019)
Bileaflet mechanical heart valves (BMHVs) are implanted in myriads of patients having valvular deficiencies. BMHVs are known to be the most durable and bio-compatible valves among mechanical prosthetic heart valves, however, they generate non-physiological blood flow pattern which is characterized by elevated shear stresses, flow separation and recirculation, and shed vortices and causes platelet activation, which leads to thrombosis.